2013
DOI: 10.1111/jvh.12193
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between polymorphisms near the IL28B gene and spontaneous HBsAg seroclearance: a systematic review and meta‐analysis

Abstract: Polymorphisms near the interleukin (IL) 28B gene have been proposed to be associated with spontaneous clearance of the hepatitis C virus. The purpose of this study was to assess the relationship between IL28B polymorphisms and the rate of spontaneous hepatitis B surface antigen (HBsAg) seroclearance by means of meta-analysis. MEDLINE/PubMed and EMBASE were utilized to identify relevant studies. Odds ratio (OR) and 95% confidence interval (CI) were analysed together to assess the strength of the association. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…As for IL‐28B polymorphisms, it seemed not to be associated with HBV natural clearance from our study, and this study again attest what we concluded previously . Also this has been validated in a recent meta‐analysis . Besides, haplotype analysis again consolidated this conclusion, which showed the trueness of our results (Tables and ).…”
Section: Discussionsupporting
confidence: 90%
“…As for IL‐28B polymorphisms, it seemed not to be associated with HBV natural clearance from our study, and this study again attest what we concluded previously . Also this has been validated in a recent meta‐analysis . Besides, haplotype analysis again consolidated this conclusion, which showed the trueness of our results (Tables and ).…”
Section: Discussionsupporting
confidence: 90%
“…This study is the first systematic review that included all relevant eligible English publications in the recent 8 years. Meanwhile, it had a larger sample size comprising 5587 cases and 4295 than previous studies [36,37]. Previous studies investigating these associations may have included low-quality publications [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…HBV ile enfekte hücrelerde, transmembran reseptörüne bağlanan IFN-λ, MHC sınıf I antijen ekspresyonunu artırır ve JAK-STAT sinyal yolağını uyarır 6 . İnsan hepatoma hücrelerinde, yüksek konsantrasyonda IFN-λ ile HBV replikasyonunun %30 oranında azaltıldığı gösterilmiş olmakla birlikte, IFN-λ'nın HBV'ye karşı antiviral aktivitesinin sınırlı olduğu bildirilmektedir 7 . Bu durum, IFN-λ'nın kodlandığı IL-28B genindeki C/T allel dağılımı ile ilişkili olabilir.…”
Section: Discussionunclassified